Climate Change Behavior Adaptation by Farmers in Mandeu Village, Raimanuk District, Belu Regency - Marina Lurdes Gonsalves; Hamza H. Wulakada; Muhammad H. Hasan (Tinta Emas Institute, 2025)
Climate change, especially erratic rainfall patterns, significantly impacts the agricultural sector, which is the main livelihood in Mandeu Village. (1) To determine the management of dry land rain-fed rice fields in Mandeu Village, Raimanuk District, Belu Regency. (2) To identify SWOT climate change in the management of dry land rain-fed rice fields in Mandeu Village, Raimanuk District, Belu Regency. (3) To determine the local wisdom adaptation strategies of farmers in facing climate change in Mandeu Village, Raimanuk District, Belu Regency. This study uses a mixed method to analyze land management and problems and farmers' adaptation strategies based on the analysis (SWOT). The results of the study show that (1) Utilization of organic fertilizer: Farmers use cow dung to improve soil nutrients, which also serves as an alternative to expensive chemical fertilizers. (2) Communal cooperation: Farmers work together to build small-scale water infrastructure such as drilled wells and mini ponds, as a response to uncertain water availability. (3) Selecting mixed rice varieties, farmers plant various rice varieties, such as the drought-resistant local Membromo rice and superior varieties such as Ciherang and Inpari, to minimize the risk of crop failure due to climate uncertainty. This study concludes that farmers in Mandeu Village have a strong ability to adapt to climate change thanks to local wisdom passed down through generations. Their strategy focuses on diversification, combining traditional practices and adopting adaptive crop varieties.